Problems faced by Students in Public Universities in Nigeria and the Way Forward - Ogunode Niyi Jacob; Audu Elizabeth; Godwin Ndubuisi Ahaotu (Jurnal Sinestesia, 2020)
The university education is designed to provide post-secondary school education for all eligible Nigerians. The Students in the Nigerian public universities are faced with many problems. The article discusses problems Nigerian public universities students faced as they are carrying out their academic activities across the country. The article used secondary data which was sourced from print material and online publications. The article identified inadequate infrastructural facilities, shortage of lecturers, unstable academic calendar, academic corruption, insecurity, financial problems and poor participation in universities management. To solve these challenges, this article recommends: that the government should increase the funding of students service programmes, provide adequate infrastructural facilities, employ more academic staff, provide adequate security in the schools, ensure stable academic calendar, institutionalize law against sexual harassment, provide proper orientation programmes to discourage students on cult related activities, ensure effective supervision of teaching and learning as well as provision of scholarship grants to students.